Penyuluhan Kesehatan Stimulasi Tubuh Kembang Dengan Pijat Bayi Padjajaran Kertapati Kota Palembang Provinsi Sumatera Selatan - Riski, Merisa; Dharmayanti, Reffi; Rahmadhani, Sendy Pratiwi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Babies are assets that are beneficial for economic growth and sustainable development of a country because they are the life expectancy of families and nations. Based on the Decree of the Minister of Health Number 28 of 2017 concerning Licensing and Implementation of Midwife Practice, it is stated that midwives have the authority. Monitoring the growth and development of babies, toddlers and preschool children includes weighing activities, head circumference measurements, height measurements, early detection stimulation and early intervention for developmental deviations in toddlers using the Pre-Developmental Screening Questionnaire (KPSP). Counseling and counseling includes providing communication, information, Journal of Digital Community Service (JUPED) | e-ISSN: 2828-3503 Volume 1, Number 3, August 2022 16 education (KIE) to mothers and families about newborn care, exclusive breastfeeding, danger signs in newborns, health services, immunizations, balanced nutrition, PHBS, and grow. Baby massage is a form of stimulation for a child's body and development. Through baby massage, comfortable and safe communication will occur between mother and baby.